Vital sign monitoring during out‐of‐hospital pediatric advanced airway management. Issue 6 (2nd October 2020) - Hansen, Matt; White, Lynn; Whitmore, Geneva; Lin, Amber; Walker, Rob
Abstract: Objective: To evaluate physiologic monitoring in pediatric patients undergoing out‐of‐hospital advanced airway management. Methods: Retrospective case series of pediatric patients (<18 years) with advanced airways placed in the out‐of‐hospital setting. Patients given cardiopulmonary resuscitation (CPR) or defibrillation before the first advanced airway attempt were excluded. Reviewers abstracted physiologic data from the patient monitor files and patient care reports. The primary outcome was the proportion of time pulse oximetry was in place during airway management. Other outcomes included the proportion of time ECG monitoring and waveform end‐tidal capnography were in place as well as the incidence of oxygen desaturation events. Results: We evaluated 23 pediatric patients with a mean age of 10.7 years (SD 6.5). Eleven of 18 (61%) children with medication‐facilitated intubation had pulse oximetry in place when the first medication was documented as given. Eight of 18 (44%) had ECG monitoring, 12 of 18 (66%) had waveform capnography, and 5 of 18 (28%) had a blood pressure check within the 3 minutes before receiving the first medication. In the 3‐minute preoxygenation phase, pulse oximetry was in place for an average of 1.4 minutes (47%, SD 0.37) and a visible photoplethysmogram (PPG) waveform obtained from the pulse oximeter was present for 0.6 minutes (20%, SD 0.34). During airway device placement, pulse oximetry was in place 73% (SD 0.39) of the time and 30% (SD 0.41) of the time there was a visible PPG waveform. Conclusions: Pediatric patients had critical deficits in physiologic monitoring during advanced airway management.